Is there a relationship between suicidal intent and lethality in deliberate self‐poisoning? - Gjelsvik, B; Heyerdahl, F; Holmes, J; Lunn, D; Hawton, K (Wiley, 2016)
The relationship between suicidal intent and lethality of deliberate self‐poisoning (DSP) episodes and their associations with suicide have yielded contradictory findings. The aims of this study were to investigate the association between patients’ suicidal intent and independently rated lethality of DSP episodes, and whether the association changes over time. Eighty‐nine DSP patients were investigated longitudinally. Self‐reported suicidal intent, including perceived likelihood of dying, wish to die, and whether or not the DSP was considered a suicide attempt, was measured at the time of the index episode (t1), 3 months (t2), and 12 months (t3) later. Lethality was assessed independently by three clinical toxicologists. Lethality was significantly associated with patients’ reported wish to die (p = .01) and perceived likelihood of dying (p = .04) at t1, but not at t2 and t3. No association was found between whether the episode was considered a suicide attempt or not and lethality at t1, t2, or t3. Lethality and suicidal intent should be considered as largely separate dimensions of self‐harm. Clinicians should bear this in mind during clinical assessment, especially regarding historical information.